2011
DOI: 10.1145/2034594.2034598
|View full text |Cite
|
Sign up to set email alerts
|

A Hough-transform-based anomaly detector with an adaptive time interval

Abstract: Internet traffic anomalies are a serious problem that compromises the availability of optimal network resources. Numerous anomaly detectors have recently been proposed, but maintaining their parameters optimally tuned is a difficult task that discredits their effectiveness for daily usage. This article proposes a new anomaly detection method based on pattern recognition and investigates the relationship between its parameter set and the traffic characteristics. This analysis highlights that constantly achievin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Further- Table 1: Heuristics labelling the traffic corresponding to a set of alarms into three categories ("Attack", "Special", and "Unknown"). These are originated from the anomalies previously reported [3,9] more, the majority of points are close to the "normal" reference point, and thus, far from the "abnormal" one. In order to understand where anomalies are located in the space, we then perform a breakdown of MAWILab anomalies regarding a heuristic-based classification.…”
Section: Scann Combination Methods Analysismentioning
confidence: 68%
See 2 more Smart Citations
“…Further- Table 1: Heuristics labelling the traffic corresponding to a set of alarms into three categories ("Attack", "Special", and "Unknown"). These are originated from the anomalies previously reported [3,9] more, the majority of points are close to the "normal" reference point, and thus, far from the "abnormal" one. In order to understand where anomalies are located in the space, we then perform a breakdown of MAWILab anomalies regarding a heuristic-based classification.…”
Section: Scann Combination Methods Analysismentioning
confidence: 68%
“…This technique has been applied to several domains including anomaly detection of backbone traffic [9]. The approach proposed in [9] consists of first, monitoring the traffic in a 2-D scatter plot where the anomalous traffic appears as "lines", and second, identifies the anomalies with the Hough transform. The original data is retrieved from the identified plots, and the alarms reported by this method are aggregated sets of flows.…”
Section: Hough Transformmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently there are a few studies on tuning specific models online [5,8,15]. The work in [15] examined the sensitivity of PCA to parameter settings and found that minor changes to the parameter settings increased the false positive rate by a factor of three or more.…”
Section: Related Workmentioning
confidence: 99%
“…A method for automatically learning optimal parameter setting and dynamically adapting the learning period was proposed. Fontugne et al described a Hugh transform method for anomaly detection that also automatically adjusts a parameter set in regards to the traffic fluctuations [5].…”
Section: Related Workmentioning
confidence: 99%